What Aspects of Rural Life Contribute to Rural‐Urban Health Disparities in Older Adults? Evidence From a National Survey. Issue 3 (29th November 2017) - Cohen, Steven A.; Cook, Sarah K.; Sando, Trisha A.; Sabik, Natalie J.
Abstract: Purpose: Rural‐urban health disparities are well‐documented and particularly problematic for older adults. However, determining which specific aspects of rural or urban living initiate these disparities remains unclear. The purpose of this study was to assess associations between place‐based characteristics of rural‐urban status and health among adults age 65+. Methods: Data from the 2012 Behavioral Risk Factor Surveillance System were geographically linked to place‐based characteristics from the American Community Survey. Self‐reported health (SRH), obesity, and health checkup within the last year were modeled against rural‐urban status (distance to nearest metropolitan area, population size, population density, percent urban, Urban Influence Codes [UIC], Rural‐Urban Continuum Codes [RUCC], and Rural‐Urban Commuting Area [RUCA]) using generalized linear models, accounting for covariates and complex sampling, overall, and stratified by area‐level income. Findings: In general, increasing urbanicity was associated with a reduction in negative SRH for all 7 measures of rural‐urban status. For low‐income counties, this association held for all measures and characteristics of rural‐urban status except population density. However, for high‐income counties, the association was reversed—respondents living in areas of increasing urbanicity were more likely to report negative SRH for 4 of the 7 measures (RUCC, UIC, RUCA, and percent urban). Findings were mixed for the outcome of obesity, where rural areas had higher levels, except in low‐income counties, where the association between rurality and obesity was reversed (OR 1.033, 95%CI: 1.002‐1.064). Conclusion: These results suggest that rural‐urban status is both a continuum and multidimensional. Distinct elements of rural‐urban status may influence health in nuanced ways that require additional exploration in future studies.